Researching school experience : ethnographic studies of teaching and learning - Hammersley, Martyn; Nias, Jennifer (Falmer Press, 1999)
There is a tendency in much educational thinking to view pupils in passive terms, as the material on which schools operate. This damaging view is challenged here. Significant recent research shows the effects of changing educational conditions on the experience of teaching and learning in schools. By redressing the balance and acknowledging the affective side of pupils and their learning, this book shows that improved understanding leads to improved teaching. Contributions from Stephen Ball, Martyn Descombe, Ann Filer, Andy Hargreaves, Bob Jeffrey, Geoff Troman, Andrew Pollard and Peter Woods.